2021
DOI: 10.3390/f12121796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urbanization on the Dynamics and Equity of Access to Urban Parks from 2000 to 2015 in Beijing, China

Abstract: Urban parks provide multiple ecosystem services as an important element of the urban space and improve human health and wellbeing. This study used the Gaussian-based 2SFCA method to evaluate the spatiotemporal distribution of and changes in park accessibility within the Sixth Ring Road in Beijing over 15 years. The study also used bivariate correlation analysis to analyze the relationship between urbanization factors and park access. The results showed that the overall park accessibility in both quantity and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Additionally, the evaluation also took into account various travel manners to satisfy different residents' travel needs to access different PGSs. For the demographic data used in the evaluation, the subdistrict-level population data were more detailed than the district-level data used in previous research [42]. From the perspective of research objects, previous similar studies have typically used the per capita area index as the capacity standard for all PGSs, without distinguishing PGS types [72,73].…”
Section: Effectiveness Of Pgs Accessibility Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the evaluation also took into account various travel manners to satisfy different residents' travel needs to access different PGSs. For the demographic data used in the evaluation, the subdistrict-level population data were more detailed than the district-level data used in previous research [42]. From the perspective of research objects, previous similar studies have typically used the per capita area index as the capacity standard for all PGSs, without distinguishing PGS types [72,73].…”
Section: Effectiveness Of Pgs Accessibility Evaluationmentioning
confidence: 99%
“…Kong et al analyzed the effect of urbanization on the accessible equity of urban parks in Beijing from 2000 to 2015, and they concluded that urbanization impacted the number and accessibility of parks positively. However, there existed an inequity in park access in some regions [42]. The Gini coefficient and the Lorenz curve are commonly used in economics to measure the income disparity among residents of a country or region.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the fast replacement of vegetated spots with infrastructures and buildings has been associated with the spreading of diseases among urban citizens [12]. Therefore, healthy and green cities should be the criteria to ensure a healthy population [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [11] reported that indeed, not only the presence of greenness is important, but the accessibility to it is also a key factor for an ideal living space, even in cities rich in green spaces [13]. Accessibility at walking distance is imperative for enhancing the frequent fruition of vegetated and restorative areas because it encourages more frequent short trips [16].…”
Section: Introductionmentioning
confidence: 99%
“…A recent comparative study of 290 Chinese cities revealed ubiquitous differences in UGS exposure between old and newly urbanized areas [8]. Rapidly urbanizing cities have been confronted with the sustainability issue of urban green system development and adding new parks might cause the increase in nearby housing prices and subsequent neighboring gentrification [9,10]. Although this inequity has been quantified and mapped, the underlying mechanisms of UGS access inequity and potential mitigation measures are not fully understood.…”
Section: Introductionmentioning
confidence: 99%